Modeling of the scientific and industrial complex structure in the digital economy - Boev, Alexey Gennadievich (Vestnik Permskogo universiteta. Seria Ekonomika = Perm University Herald. Economy, 2021)
The dynamic development of the digital economy creates new business conditions that catalyze cross-industry cooperation of enterprises and accelerate technology transfer between various market entities. This determines the need for the efficient integrated structures in the industrial sector of Russia with high scientific, innovative, digital, and production capacity. The purpose of the research is to develop and operationalize a competitive model of the scientific and industrial complex in the digital economy. The content of the scientific and industrial complex is determined, and the differences between the complex and the industrial cluster are identified. The competitive advantages of a scientific industrial complex in relation to autonomous enterprises are highlighted. The scientific novelty and practical significance of the study unfold in the development of theoretical provisions and structural and functional parameters of the model of the scientific and industrial complex in the digitalization of the social economic systems, as well as a cluster analysis based methodological approach to its operationalization. A methodological approach to the operationalization of the model of scientific and industrial complexes performing in the digital economy includes four stages: 1) identifying the prerequisites for the integration; 2) choosing the goals for establishing a complex; 3) enterprises clusterization and modeling of scenarios for establishing a complex; 4) development of a complex’s functioning and development mechanism. The basic, industrial and technological, innovative digital, institutional and managerial, structural, financial and market criteria for clustering enterprises and organizations to establish a complex have been worked out. The approach was tested and options for establishing scientific and industrial complexes were modeled from cluster analysis of 37 enterprises of the Central Chernozem region of Russia by the G-means method. With the results of the analysis in mind, the authors recommended to set up radio-electronic, electrical engineering complexes in Voronezh region and a machine-building complex in Lipetsk region. The article offers a list of members, goals, types of strategies, integration projects and expected results of the modeled complexes performance. The model of the scientific and industrial complex and the approach to its operationalization can become a methodological tool for the management of enterprises when some options for setting up, organization types and scenarios for the development of integrated structures in the industry of Russia are considered. Further research is seen to be in developing the models of strategic and sustainable development during digital transformation of scientific and industrial complexes, as well as in developing organizational and economic mechanisms for institutional transformations of industrial enterprises in the digital economy. Keywords model of the scientific and industrial complex, integrated structures, scientific cooperation, innovative development, cluster, digital transformation, modeling, G-means method, digital economy. References 1. Boev A.G. Formirovanie nauchno-promyshlennykh kompleksov v usloviyakh tsifrovoi ekonomiki [Formation of scientific and industrial complexes in the digital economy]. Mir ekonomiki i upravleniya [World of Economics and Management], 2021, vol. 21, no. 1, pp. 119–135. (In Russian). doi: 10.25205/2542-0429-2021-21-1-119-135. 2. Zhu S., He С., Zhou Y. How to jump further and catch up? Path breaking in an uneven industry space. Journal of Economic Geography, 2017, no. 3, pp. 521–545. 3. Kotter D. Vperedi peremen: kak uspeshno provesti organizatsionnye preobrazovaniya [Leading Change]. Moscow, Al'pina Pablisher Publ., 2019. 288 p. (In Russian). 4. Deming E. Menedzhment novogo vremeni: Prostye mekhanizmy, vedushchie k rostu, innovatsiyam i dominirovaniyu na rynke [The New Economics for Industry, Government, Education]. Moscow, Al'pina Pablisher Publ., 2019. 182 p. (In Russian). 5. Bartelsman E., Haltiwanger J., Scarpetta S. Cross-country differences in productivity: The role of allocation and selection. American Economic Review, 2013, vol. 103, no. 1, pp. 305–334. 6. Kleiner G.B. Promyshlennye ekosistemy: vzglyad v budushchee [Industrial ecosystems: Foresight]. Ekonomicheskoe vozrozhdenie Rossii [The Economic revival of Russia], 2018, no. 2 (56), pp. 53–62. (In Russian). 7. Marshall A. Osnovy ekonomicheskoi nauki: per. s angl [Principles of Economics: Translated from English]. Moscow, Eksmo Publ., 2007. 832 p. (In Russian). 8. Perroux F. Note on the concept of growth poles. Regional economics: Theory and practice, D. McKee et al (eds.), 1970, pp. 93–103. 9. Porter M. Mezhdunarodnaya konkurentsiya. Konkurentnye preimushchestva stran [The Competitive Advantage of Nations]. Moscow, Mezhdunarodnye otnosheniya – Moskva Publ., 2009. 896 p. (In Russian). 10. Weber A. Theory of the location of industries. Chicago, The University of Chicago Press, 1929. 256 p. 11. Soulie D. Filieres de production et integration vertical. Annales des Mines, Janvier, 1989, pp. 21–28. 12. Schumpeter J.A. The theory of economic development. New York, Oxford University, 1934. 13. Kolosovskii N.N. Voprosy tipologii proizvodstvenno-territorial'nykh sochetanii (kompleksov). Tezisy doklada [Issues of typology of industrial territorial structures (units). Conference abstracts]. Teoriya ekonomicheskogo raionirovaniya [Theory of economic regionalization], Moscow, Mysl' Publ., 1969, pp. 142–148. (In Russian). 14. Graham L. Will Russia be able to compete? The history of innovations in tsarist, Soviet and modern Russia. Moscow, Mann, Ivanov and Ferber, 2014. 272 p. 15. Adner R. Ecosystem as structure: An actionable construct for strategy. Journal of Management, 2017, vol. 43, no. 1, pp. 39–58. doi: 10.1177/0149206316678451. 16. Gitel'man L.D. Menedzhment – tvoya rabota. Deistvui na operezhenie! [Management is your work. Act forward!]. Moscow, Infra-M Publ., 2018. 544 p. (In Russian). 17. Kotter J.P. Accelerate: Building strategic agility for a faster-moving world. Harvard Business Review Press, 2014. 224 p. 18. Karlik A.E., Platonov V.V. Mezhotraslevye territorial'nye innovatsionnye seti [Cross-industry spatially localized innovation networks]. Ekonomika regiona [Economy of Region], 2016, vol. 12, iss. 4, pp. 1218–1232. (In Russian). doi: 10.17059/2016-4-22. 19. Anisimov Yu.P., Zhuravlev Yu.V., Kuksova I.V., Balabanova E.I., Zhil'nikov A.Yu., Elagina T.V. Prostranstvennyi analiz razvitiya innovatsionnogo potentsiala predpriyatii [Spatial analysis of the development of innovative potential of enterprises]. Vestnik Voronezhskogo gosudarstvennogo universiteta inzhenernykh tekhnologii [Proceedings of Voronezh State University of Engineering Technologies], 2019, no. 81 (1), pp. 391–396. (In Russian). doi: 10.20914/2310-1202-2019-1-391-396. 20. Syshchikova E.N. Teoretiko-metodologicheskii podkhod k opredeleniyu sushchnosti i soderzhaniya modernizatsii sistemy upravleniya naukoemkim predpriyatiem [Theoretical methodological approach to the nature and content of modernization of a science-based enterprise management system]. Ekonomika i predprinimatel'stvo [Journal of Economy and Entrepreneurship], 2020, no. 8 (121), pp. 860–863. (In Russian). 21. Boev A.G. K voprosu o soderzhanii i differentsiatsii ponyatii promyshlennyi kompleks, klaster i industrial'nyi park [On the issue of the content and differentiation of the concepts industrial complex, cluster and industrial park]. Organizator proizvodstva [Production Organizer], 2020, vol. 28, no. 2, pp. 7–17. (In Russian). doi: 10.25987/VSTU.2020.97.45.001. 22. Vorob'ev V.P., Lipatnikov V.S., Rozanova S.K., Uvarova L.F. Innovatsionnoe razvitie promyshlennykh kompleksov na osnove klasternogo podkhoda [Cluster approach based innovative development of industrial units]. Saint Petersburg, Petropolis Publ., 2011. 144 p. (In Russian). 23. Ermolenko A.A. Sub"ektnaya tselostnost' rossiiskoi ekonomiki: vzglyad cherez prizmu teorii integrirovannykh sub"ektov [The subject integrity of Russian economy from the perspective of the theory of integrated subjects]. Vestnik Volgogradskogo gosudarstvennogo universiteta. Seriya 3: Ekonomika. Ekologiya [Science Journal of VolSU. Global Economic System], 2018, vol. 20, no. 2, pp. 5–15. (In Russian). doi: 10.15688/jvolsu3.2018.2.1. 24. Sukharev O.S. Ekonomicheskaya teoriya institutsional'nykh izmenenii: podkhody k modelirovaniyu korrektsii i disfunktsii institutov [Economic theory of institutional changes: Approaches to modeling corrections and dysfunctions of institutions]. Zhurnal ekonomicheskoi teorii [Russian Journal of Economic Theory], 2018, vol. 15, no. 2, pp. 276–290. (In Russian). doi: 10.31063/2073-6517/2018.15-2.12. 25. Il'yasov B.G., Makarova E.A., Zakieva E.Sh., Gabdullina E.R. Metodologicheskie osnovy modelirovaniya i intellektual'nogo upravleniya promyshlennym kompleksom kak slozhnym dinamicheskim mnogoagentnym ob"ektom [Methodological foundations of modeling and intelligent management of an industrial complex as a complex dynamic multi-agent object]. Sovremennye naukoemkie tekhnologii [Modern High Technologies], 2020, no. 11-2, pp. 288–293. (In Russian). doi: 10.17513/snt.38376. 26. Sistemnoe modelirovanie i analiz mezo- i mikroekonomicheskikh ob"ektov / otv. red. V.V. Kuleshov i N.I. Suslov [System Modeling and Analysis of Mezo- and Micro-Economic Objects. Editor-in-Chief V.V. Kulishov and N.I. Syslov]. Novosibirsk, IEOPP SO RAN Publ., 2014. 488 p. (In Russian). 27. Topoleva T.N. Formirovanie innovatsionnoi modeli razvitiya predpriyatii promyshlennogo kompleksa [Formation of innovative model of industrial complex enterprises development]. Vestnik PNIPU. Sotsial'no-ekonomicheskie nauki [PNRPU Sociology and Economics Bulletin], 2018, no. 4, pp. 220–232. (In Russian). doi: 10.15593/2224-9354/2018.4.18. 28. Grebenkin I.V., Botkin I.O. Otsenka regional'nykh klasterov v mashinostroenii [Assessment of regional clusters in mechanical engineering]. Vestnik Udmurtskogo universiteta. Ekonomika i pravo [Bulletin of Udmurt University. Series Economics and Law], 2017, vol. 27, no. 4, pp. 14–22. (In Russian). 29. Barsegyan N.V., Shinkevich A.I. Modelirovanie organizatsionnoi struktury upravleniya promyshlennym predpriyatiem (na primere AO «KVART») [Modeling of the organizational structure of industrial enterprise management (for example, JSC “KVART”)]. Izvestiya Samarskogo nauchnogo tsentra Rossiiskoi akademii nauk [Izvestia of Samara Scientific Center of the Russian Academy of Sciences], 2020, vol. 22, no. 2, pp. 91–99. (In Russian). doi: 10.37313/1990-5378-2020-22-2-91-99. 30. Boev A.G., Kolesnikova V.B., Kolodyazhnaya A.A. Typology of institutional transformation strategies of industrial complexes in the digital economy. Proceedings of the 2nd International Scientific and Practical Conference on Digital Economy (ISCDE 2020), 2020, pp. 447–454. doi: 10.2991/aebmr.k.201205.075. 31. Boev A.G. Metodika otsenki strategii i khoda institutsional'nykh preobrazovanii promyshlennykh kompleksov v usloviyakh tsifrovoi ekonomiki [Methodology for evaluating the strategy and progress of institutional transformations of industrial complexes in the digital economy]. Strategicheskie resheniya i risk-menedzhment [Strategic Decisions and Risk Management], 2020, vol. 11, no. 3, pp. 250–261. (In Russian). doi: 10.17747/2618-947X-2020-3-250-261. 32. Boev A.G., Anisimov Yu.P., Voronin S.I. Protsedura vnedreniya tsifrovoi platformy promyshlennogo kompleksa na osnove metodov proektnogo upravleniya [Procedure for implementing the digital platform of the enterprise based on project management methods]. FES: Finansy. Ekonomika. Strategiya [FES: Finance. Economy. Strategy], 2021, vol. 18, no. 1, pp. 5–17. (In Russian). 33. Mintzberg H. Bedtime stories for managers. Oakland (USA), Berrett-Koehler Publishers, 2019. 200 p. 34. Il'in I.V., Svetun'kov S.G., Kalyazina S.E., Bagaeva I.V. Osnovnye trendy tsifrovoi transformatsii rossiiskogo biznesa [Main trends of the digital transformation of Russian business]. Nauka i biznes: puti razvitiya [Science and Business: Ways of Development], 2019, no. 7 (97), pp. 137–143. (In Russian). 35. Krylov V.E. Sostoyanie sotsial'no-ekonomicheskoi sistemy: problemy modelirovaniya i osobennosti identifikatsii parametrov modeli [The state of the socio-economic system: Modeling problems and features of identification of model parameters]. Ekonomika i upravlenie: problemy, resheniya [Economics and Management: Problems, Solutions], 2018, vol. 5, no. 9, pp. 25–31. (In Russian). 36. Drucker P. Effektivnyi rukovoditel' [The Effective Executive]. Moscow, Mann, Ivanov i Ferber: Eksmo Publ., 2019. 240 p. (In Russian).